The fasciacytes: A new cell devoted to fascial gliding regulation. Issue 5 (14th April 2018) - Stecco, Carla; Fede, Caterina; Macchi, Veronica; Porzionato, Andrea; Petrelli, Lucia; Biz, Carlo; Stern, Robert; De Caro, Raffaele
Abstract : Hyaluronan occurs between deep fascia and muscle, facilitating gliding between these two structures, and also within the loose connective tissue of the fascia, guaranteeing the smooth sliding of adjacent fibrous fascial layers. It also promotes the functions of the deep fascia. In this study a new class of cells in fasciae is identified, which we have termed fasciacytes, devoted to producing the hyaluronan‐rich extracellular matrix. Synthesis of the hyaluronan‐rich matrix by these new cells was demonstrated by Alcian Blue staining, anti‐HABP (hyaluronic acid binding protein) immunohistochemistry, and transmission electron microscopy. Expression of HAS2 (hyaluronan synthase 2) mRNA by these cells was detected and quantified using real time RT‐PCR. This new cell type has some features similar to fibroblasts: they are positive for the fibroblast marker vimentin and negative for CD68, a marker for the monocyte‐macrophage lineage. However, they have morphological features distinct from classical fibroblasts and they express the marker for chondroid metaplasia, S‐100A4. The authors suggest that these cells represent a new cell type devoted to the production of hyaluronan. Since hyaluronan is essential for fascial gliding, regulation of these cells could affect the functions of fasciae so they could be implicated in myofascial pain. Clin. Anat. 31:667–676, 2018. © 2018 Wiley Periodicals, Inc.